4-(x-8)=3x+2(x-1)

Simple and best practice solution for 4-(x-8)=3x+2(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-(x-8)=3x+2(x-1) equation:


Simplifying
4 + -1(x + -8) = 3x + 2(x + -1)

Reorder the terms:
4 + -1(-8 + x) = 3x + 2(x + -1)
4 + (-8 * -1 + x * -1) = 3x + 2(x + -1)
4 + (8 + -1x) = 3x + 2(x + -1)

Combine like terms: 4 + 8 = 12
12 + -1x = 3x + 2(x + -1)

Reorder the terms:
12 + -1x = 3x + 2(-1 + x)
12 + -1x = 3x + (-1 * 2 + x * 2)
12 + -1x = 3x + (-2 + 2x)

Reorder the terms:
12 + -1x = -2 + 3x + 2x

Combine like terms: 3x + 2x = 5x
12 + -1x = -2 + 5x

Solving
12 + -1x = -2 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
12 + -1x + -5x = -2 + 5x + -5x

Combine like terms: -1x + -5x = -6x
12 + -6x = -2 + 5x + -5x

Combine like terms: 5x + -5x = 0
12 + -6x = -2 + 0
12 + -6x = -2

Add '-12' to each side of the equation.
12 + -12 + -6x = -2 + -12

Combine like terms: 12 + -12 = 0
0 + -6x = -2 + -12
-6x = -2 + -12

Combine like terms: -2 + -12 = -14
-6x = -14

Divide each side by '-6'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| 2+6x+3x=65 | | r+2+9=12 | | 9y+7=88 | | -x+2x+7x=74 | | -47=5x+2x+2 | | 5(z-1)(-z-4)=0 | | 6d+5=4d+9 | | 5(v-4)-5=-2(-4v+5)-9v | | 2(x+3)=x+3 | | 2w+3w-324=0 | | 3(y-1)=2 | | -32=4(x-1) | | -8+x-4x=-23 | | -8x+24=-5x-9 | | 4x+10=32 | | 35=4x+2x-1 | | 18(5/6x-1/3)+14(1/2x-5/7)=0 | | 2y-10-y=4 | | f(x)=5lnx | | (12-9x).33=17 | | 11tsquare+1t-10=0 | | 6x+3(5x+13)=186 | | 3x+1=10x+4 | | y=-9x^2-36x-35 | | 3y+8=7+4y | | (12-9x).667=17 | | x=42-8y | | g(x)=x-8 | | 2(5x-4)-(3x+2)+11=-3(-5+10)+3x-6(4x-3) | | x=-42-8y-18x-4-8y | | 62-76x=-8x-738 | | 5x+7(x-5)-3(y-5)=12x-3y-20 |

Equations solver categories